Aspects of aluminum alloy utilization in vertical cylindrical tank construction - Shuvalov Alexander; Mitrofanov Dmitry; Doroshin Ivan; Kazaryan Ruben (BIO Web of Conferences)
Background: One of the most popular structures in the production and transportation of oil and petroleum products are vertical cylindrical tanks. Nowadays, the greatest demand is for tanks whose main structural material is steel. When working at low temperatures, the performance of steel deteriorates, ductility and toughness decrease, which leads to various emergency situations, while aluminum alloys are free of these disadvantages and their performance improves as the temperature decreases. Objective: First: determination of the economic effect when using aluminum alloy 1915T in the construction of vertical cylindrical tanks; second: determination of structural and technological advantages when using aluminum alloy 1915T over steel 09G2S. Methods: Methodology for calculation and design of vertical cylindrical tanks made of steel 09G2S and aluminum alloy 1915T. Results: The characteristics of aluminum alloy 1915T when used at low temperatures have been revealed. An algorithm for calculating and designing tanks using aluminum alloy 1915T and steel 09G2S as materials has been determined. A technology for constructing tanks from both materials has been developed, and labor intensity has been calculated. Conclusion: Calculation of labor intensity revealed that welded joints of aluminum structures differ in labor intensity from steel ones, while the overall labor intensity of constructing a tank made of aluminum alloy 1915T is lower.